heARtbeat: Augmented reality for teaching electrocardiogram electrode placement - Cathal Breen; William Hurst (Computers & Education: X Reality, 2025)
The 12-lead Electrocardiogram (ECG) is currently one of the most widely used, operator-dependent clinical skills in healthcare. To enable correct interpretation of ECG recordings, electrodes must be placed in specific anatomic locations on the chest, legs and arms. Traditional learning practices of ECG electrode placement are not standardized and burdening on faculty staff and resources. Thus, misplacement of ECG electrodes affects the accuracy of interpretation and referral to medical treatments. Augmented Reality (AR) offers a safe and scalable metric for students to learn and practice various procedures and skills by creating hyper-realistic simulations. Yet, within the healthcare domain, the main applications of AR are in the field of surgery, rehabilitation, and anatomy teaching. Therefore, this article documents the design of an AR application for teaching ECG electrode placement and the tool's Alpha evaluation by means of an expert validation and case study trial. Users of the application found it to be Inspiring (5.0) and Educational (4.9) but less effective in terms of User Friendliness (2.8) on a 7-point Likert scale. Regarding the educational potential, 57 % of the end users found the tool to increase their knowledge of ECG placement.